The State Of Regime Change And Systemic Change In The Electoral Politics Of Malaysia And The Philippines: What Has Malaysia And The Post-Marcos Philippines Learnt? - Fong, John Wai Kinn (2021)
This study explores and analyses the differences in the change of government in the electoral politics. The democratic rule for most of the South East Asia nations particularly in Malaysia and the Philippines, were interpreted differently by politicians, the elites, and the leaders. Instead, they have chosen to consolidate the power that they acquired through elected office and the immense wealth that comes with it. As elections remain a crucial attribute of democracy in Malaysia and the Philippines since granting independence, absolute authoritarianism is impossible, therefore, electoral authoritarianism was introduced as it has the ability to mimic many fundamental attributes of democracy and possesses sufficient indicators of democracy. As the regimes began tightening its grip and employed a higher level of electoral authoritarianism over the years, the people began mobilizing towards challenging the regime and demanded that the power of rule returns to the people. Depending on the scale of mobilization and the electoral reform movements, regime change, and systemic change occurred in Malaysia and the Philippines, respectively. The great challenge is now how much of these improved changes were actually permanent after a change of government or even so, will they be able to stand the test of time or to stand against any future changes in the government? This research uses secondary source and qualitative method; in-depth one-to-one interviews are conducted with 10 identified respondents who are familiar with Malaysia and the Philippines political and electoral system, respectively.